The Strategic Role of The Indonesian Diaspora in Supporting a Just Energy Transition: Education, Technology, and Ethics within a Post-Normal Science Framework - Muhammad Nadzara, Arzqilail (UIN Sunan Gunung Djati Bandung, 2025)
Environmental degradation from fossil fuels has triggered a global climate crisis, making a just energy transition imperative. Indonesia, with vast renewable energy potential, faces significant challenges in realizing this transition. This study examines the strategic role of the Indonesian diaspora in advancing a just energy transition through collaboration in education, renewable energy technology transfer, and environmental ethics. Using a qualitative–descriptive approach, the research integrates Post-Normal Science and Tactical Diaspora frameworks and analyzes secondary data from scientific journals, policy documents, international reports, and credible media. The findings show that diaspora communities act as knowledge mediators and ethical agents by facilitating curriculum reform in sustainability education, supporting renewable energy technology co-development and pilot projects, and promoting justice-oriented environmental norms. The study proposes diaspora-driven initiatives such as digital education platforms, community-based green pilot projects, and participatory climate financing to enhance inclusivity and justice in the transition process. These contributions underscore the diaspora’s capacity to bridge global expertise with local needs, ensuring Indonesia’s energy transformation proceeds equitably and inclusively while minimizing socio-economic disparities and advancing climate justice. This study contributes theoretically by linking Post-Normal Science and Tactical Diaspora frameworks.